Incidence, characteristics, pattern and management of ovarian cancer in Abuja, Nigeria - Ayogu, Malachy Emeka; Abdullahi, Habiba Ibrahim; Eze, Innocent O. (International Journal of Research in Medical Sciences, 2020)
Background: The prevalence of ovarian cancer is thought to be increasing with huge burden of the disease with no comprehensive cancer center that can offer appropriate care in developing countries. However, little is known about the incidence, pattern and outcome of this disease in Abuja, Nigeria. Therefore, the aim of this study was to review the pattern of care offered to patients with ovarian cancer in our center and to evaluate patients’ outcome. Methods: This was a retrospective review of all the patients with histologically confirmed ovarian cancers admitted to the gynecological ward of the hospital over a period of 5 years. Relevant information was extracted from the ward register and patients medical case records. Data were analyzed using statistical package for social science version 23 and results were then presented in tables and chart. Results: Ovarian cancers constituted 19.6% and 5.6% of all gynecological cancers and all gynecological admissions respectively. The mean age at presentation was 50.2±8.5 years and premenopausal 32 (55%) constituting the majority. A large proportion 43 (74.1%) of the patients were parous. The commonest symptoms at presentation were abdominal swelling (86.2%), and abdominal pain (53.4%) with the majority 38 (65.5%) presenting in an advanced stage. The commonest histological type of ovarian cancers was epithelial accounting for 30 (51.7%) of all ovarian cancers. Common treatment modality was surgery and chemotherapy and majority 32 (55.3%) of the patients had cytoreductive surgery with 19 of them having optimum cytoreduction and 33 (57%) benefitted from chemotherapy. Lost to follow- up was significantly high (55%) and mortality rate was 15.5%. Conclusion: Cases of ovarian cancers are on the increase. Women presented at an advanced stage of the disease, which resulted in short survival times. Failure of optimal management was also worsened by poor compliance to treatment with high patients’ default rate.